The Russian-Ukrainian Crisis and its Repercussions on the International System - ben Gablia, Almaki Mohammed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The Russian-Ukrainian crisis, which erupted widely in February 2022, is one of the most significant geopolitical transformations of the 21st century. It has reshaped the international order and raised fundamental questions about the future of international relations, the balance of power, and the concept of sovereignty. The crisis began with a large-scale Russian military escalation against Ukraine, driven by historical, security, and geopolitical factors, most notably Moscow’s rejection of Kyiv’s accession to NATO and its view of Ukraine as part of its traditional sphere of influence. This study discusses the Russian-Ukrainian crisis and its implications for the international order. It aims to analyze this crisis and its repercussions for the international order, and attempts to anticipate future scenarios for the crisis. The study also highlights the most important findings and recommendations reached.